2016
DOI: 10.1038/srep26339
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization of human stromal refractive lenticules for corneal tissue engineering

Abstract: Small incision lenticule extraction (SMILE) becomes a procedure to correct myopia. The extracted lenticule can be used for other clinical scenarios. To prepare for allogeneic implantation, lenticule decellularization with preserved optical property, stromal architecture and chemistry would be necessary. We evaluated different methods to decellularize thin human corneal stromal lenticules created by femtosecond laser. Treatment with 0.1% sodium dodecylsulfate (SDS) followed by extensive washes was the most effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 34 publications
4
64
0
1
Order By: Relevance
“…Furthermore, it has been proposed that a chemical decellularization method could be an alternative to cryopreservation of donor lenticules. 31,32 Acellular porcine corneal stroma Decellularization methods for supplementing the supply of donor corneas have gained popularity in recent years, specifically in the use of non-human (typically porcine) corneal tissue for human corneal transplantation. The use of nonhuman corneas presents an alternative to reliance on human cornea donation, as porcine corneas are readily obtainable from the food processing industry and have similar characteristics to the human cornea in terms of size, thickness and biomechanical properties.…”
Section: Human Donor Stromal Lenticulesmentioning
confidence: 99%
“…Furthermore, it has been proposed that a chemical decellularization method could be an alternative to cryopreservation of donor lenticules. 31,32 Acellular porcine corneal stroma Decellularization methods for supplementing the supply of donor corneas have gained popularity in recent years, specifically in the use of non-human (typically porcine) corneal tissue for human corneal transplantation. The use of nonhuman corneas presents an alternative to reliance on human cornea donation, as porcine corneas are readily obtainable from the food processing industry and have similar characteristics to the human cornea in terms of size, thickness and biomechanical properties.…”
Section: Human Donor Stromal Lenticulesmentioning
confidence: 99%
“…Triton X‐100 is a non‐ionic detergent and the second most commonly used detergent in corneal decellularization experiments . Its decellularization activity is based on the disruption of lipid‐to‐lipid and lipid‐to‐protein interactions, but not protein‐to‐protein interactions . The efficacy of decellularization agents greatly fluctuates with the tissue being treated.…”
Section: Decellularization Methodsmentioning
confidence: 99%
“…[17][18][19] Its decellularization activity is based on the disruption of lipid-to-lipid and lipid-to-protein interactions, but not protein-to-protein interactions. 33 The efficacy of decellularization agents greatly fluctuates with the tissue being treated. For instance, while TX is able to decellularize cartilage, corneal decellularization studies have shown great variability.…”
Section: Triton X-100 (Tx)mentioning
confidence: 99%
“…Small incision lenticular extraction (SMILE) is a growing LASIK alternative with nearly 400,000 procedures performed worldwide to date. 130 SMILE is the process of removing a stromal lenticule via FSL and subsequent manual dissection, improving refraction for myopic patients. 131 With the growing use of this technique, some groups have examined the possible use of the refractive lenticules in hyperopia, 132 keratoconus, 133 and reimplantation after SMILE.…”
Section: Corneal Lenticules For Refractive Proceduresmentioning
confidence: 99%
“…132 However, the process of lenticular preparation storage and after initial extraction is not straightforward. Corneal lenticules must be decellularized to prevent graft rejection 130 and then stored in a manner to preserve tissue integrity. 135 Currently, lenticules are measured to estimate refractive power and then matched to appropriate patients.…”
Section: Corneal Lenticules For Refractive Proceduresmentioning
confidence: 99%